ANALYSIS OF THE EFFECT OF MULTIBAND SECTOR ANTENNA TILTING CHANGES ON LTE NETWORK QUALITY AT SITE XL SUNGAI BUNDUNG MEMPAWAH - Azis, Rahman; Imansyah, Fitri; Yacoub, Redi (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2023)
Based on the facts, the lack of equity in LTE service quality is caused by several factors that exist in the BTS antenna transmission. One area that is still experiencing problems with the lack of network speed and good signal service quality is the Sungai Bundung Laut area of Mempawah Regency. In this study to optimize the transmission of LTE signals in the area, tilting measurements on sectoral antennas are needed. The purpose of this research is to analyze the actual value of tilting changes in the sectoral antenna and analyze the results of LTE signal quality at the mobile station before and after physical tunning and analyze the results of optimization of good and bad levels of LTE signal quality at the mobile station in XL site Sungai Bundung Laut Mempawah Regency. This measurement is done by adjusting the degree angle in 3 antenna sectors using physical tunning and optimization methods. In the physical tunning method, the results obtained in sector 1 are a change in the polarization of the downtilt antenna to Uptilt from 6 ° to 2 °, then a change in the Azimuth angle from 85 º to 120 º. For sector 2 there is a change in Mechanical Downtilt which is changed from 1 ° to 3 °. And in sector 3 there is a change in Electrical tilt which is from 3 ° to 4 °. Whilethe optimization method can change the results of the RSRP signal quality level for the L900 frequency before optimization the overall value is 93.10%, after optimization it becomes 96.16%, from the optimization results there is an increase of 3.05%. For SINR before optimization the overall value amounted to 90.99%, after optimization it became 96.72%, from the optimization results there was an increase of 5.73%. As for changes in RSRP at frequency L1800 before optimization, the overall value amounted to 96.23%, after optimization it became 96.98%, from the optimization results there was an increase of 0.75%. As for SINR before optimization the overall value amounted to 96.99%, after optimization it became 98.02% from the optimization results there was an increase of 1.02%.